Single-Piece Implant Systems and its Longterm Stability: An Evaluative Research - Piyush Javiya; Kandra Rajakumari; Sravya Gorrepati; Donka Srilakshmi; Manawar Ahmad Mansoor; Hina Naim Abdul; Fawaz Abdul Hamid Baig (Wolters Kluwer Medknow Publications, 2024)
Objective: The objective of this research was to compare the longstanding stability of single-piece implant systems to typical two-piece systems by analyzing patient records retrospectively. Methods: A retrospective examination of patient records from January 2010 to December 2020 was undertaken at the Department of Oral Implantology, University Hospital. The research included dental rehabilitation patients who got single- or two-piece implant systems. Patient demographics, implant features, surgical procedures, and follow-up results were extracted. Implant success rates, stability defined by resonance frequency analysis (RFA) utilizing Osstell ISQ®, and peri-implant bone loss evaluated by standardized periapical radiographs at baseline and follow-up visits were the main outcomes. Results: The research involved 320 patients (160 per cohort). The average patient age was 52.7 years, with 55% men. The mandibular region received 65% of implants, and the maxillary region the rest. Single-piece cohort A had 94.6% implant success, and two-piece cohort B 96.2%. Implant success rates were similar between cohorts (P = 0.412). The mean ISQ scores were 72.4 ± 4.8 in cohort A and 74.8 ± 5.1 in cohort B (P = 0.086). Peri-implant bone loss was 1.8 ± 0.7 mm in cohort A and 1.4 ± 0.6 mm in cohort B (P = 0.031). Conclusion: Single-piece implant systems provide a stable and successful alternative to classic two-piece systems. However, patient selection, surgical technique, and monitoring are essential to reduce peri-implant problems and improve clinical results. To improve implant dentistry patient care and evidence-based clinical practice, single-piece and two-piece implant systems' design, biomechanical features, and longstanding performance should be studied.